The Relationship Between Political Connections and Corporate Governance Quality: Evidence from Indonesia - Harianto, Sandy (Jurnal Profita: Komunikasi Ilmiah Akuntansi dan Perpajakan, 2023)
In this study, the author investigates the relationship between political connections and corporate governance quality in Indonesia, a developing country that experience significant improvement of corporate governance implementations and the nature of political connectedness to provide evidence to support the stewardship theory (complementary relationship). Using hand-picked data from Indonesian listed firms between 2010-2015 period, the author  find that politically connected firms have better corporate governance quality, measured by corporate governance index and disclosure index, than non-connected firms. Additionally, the author also find that the positive effect of political connections will be strengthened in the presence of a stronger/more independent board composition. The results of this study will be useful to government and regulators promoting the benefits of good corporate governance system. In particular, the results suggest that the nature of political connections can change from rent-seeking opportunistic behaviour (agency theory) to accountable behaviour (stewardship theory), even in an emerging country with the presence of large dominant shareholders such as Indonesia, depending on several factors in the institutional setting.